ANALISIS PENGELOLAAN LIMBAH MEDIS DI RUMAH SAKIT ANAK DAN BUNDA HARAPAN KITA JAKARTA TAHUN 2016 - Nofianti, Nofianti; Heryana, Ade; Azteria, Veza (Universitas Esa Unggul, 2020)
AbstractHarapan Kita Children and Women Hospital is a special type of hospital grade . As the national referral hospital, the operation of hospital produced a variety of medical waste that it should be managed. The goals of the research are to analyze medical waste management in â€œHarapan Kitaâ€ Children and Women Hospital. The type of research is a descriptive method with the qualitative approach with primary and secondary data. Primary data obtained using the technique of observation and in-depth interviews against the selected informants, the secondary data obtained from a review of the documents. Overall medical waste management in â€œHarapan Kitaâ€ Children and Women Hospital not yet appropriatethe regulation of hazardous waste management in health service according to PERMEN/LHK RI P.56/Menlhk-Setjen/2015. There is some mismatch at each process of management, such as reduction process not yet applied in medical waste management, medical waste disposal in the inpatient room is under the standard, the trash is in bad condition, notoptimal socialized of policies and operating procedure, and the officer bad waste compliance transportation. Immediately arrange working program, policies and operating procedure related to reducing medical waste, first priority to the procurement of the trash and intensively arrange the supervision and socialization about policies and operating procedure of medical waste management. Key words : Medical Waste, Hospital, Sanitation, AbstrakHarapan Kita adalah rumah sakit khusus ibu dan anak yang merupaka rumah sakit tipe khusus. Sebagai rumah sakit rujukan nasional, operasional rumah sakit ini menghasilkan berbagai limbah medis yang harus dikelola. Tujuan dari penelitian ini adalah untuk menganalisis pengelolaan limbah medis di Rumah Sakit Ibu dan Anak Harapan Kita. Jenis penelitian adalah metode deskriptif dengan kualitatifpendekatan dengan data primer dan sekunder. Data primer diperoleh dengan menggunakan teknik observasidan wawancara mendalam terhadap informan terpilih, data sekunder diperoleh dari ulasandokumen-dokumen. Pengelolaan limbah medis secara keseluruhan di Rumah Sakit Ibu dan Anak Harapan Kita. belum sesuai dengan peraturan pengelolaan limbah berbahaya di layanan kesehatan menurutPermen LHK RI P.56 / Menlhk-Setjen / 2015. Ada beberapa ketidaksesuaian di setiap proses manajemen,seperti proses reduksi yang belum diterapkan dalam pengelolaan limbah medis, pembuangan limbah medis diruang rawat inap di bawah standar, sampah dalam kondisi buruk, sosialisasi kebijakan tidak optimal danprosedur operasi, dan petugas kepatuhan transportasi limbah buruk. Pengaturan program kerja, kebijakan dan prosedur operasi terkait pengurangan limbah medis, pertamamemprioritaskan pengadaan sampah dan secara intensif mengatur pengawasan dan sosialisasitentang kebijakan dan prosedur operasi pengelolaan limbah medis. Kata Kunci :Sampah Rumah Sakit, Rumah Sakit, Sanitasi